2022
DOI: 10.3390/ijms232415860
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Increases Serum and White Adipose Tissue SIRT1 Expression in Mice

Abstract: Overnutrition and its sequelae have become a global concern due to the increasing incidence of obesity and insulin resistance. A ketogenic diet (KD) is widely used as a dietary treatment for metabolic disorders. Sirtuin1 (SIRT1), a metabolic sensor which regulates fat homeostasis, is modulated by dietary interventions. However, the influence of nutritional ketosis on SIRT1 is still debated. We examined the effect of KD on adipose tissue, liver, and serum levels of SIRT1 in mice. Adult C57BL/6J male mice were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…One exception is a study in the model of Dravet syndrome where increased calorie intake was accompanied by increased body weight probably resulting from improvement of other disease symptoms ( 44 ). Decreased calorie intake, accompanied by decreased body weight during nutritional ketosis was reported in a couple of studies ( 53 , 159 163 ). Taken together the majority of studies show that a KD, in comparison to standard chow, does not induce a spontaneous reduction in food intake.…”
Section: Behavioral Effects Of Kd Treatmentmentioning
confidence: 85%
“…One exception is a study in the model of Dravet syndrome where increased calorie intake was accompanied by increased body weight probably resulting from improvement of other disease symptoms ( 44 ). Decreased calorie intake, accompanied by decreased body weight during nutritional ketosis was reported in a couple of studies ( 53 , 159 163 ). Taken together the majority of studies show that a KD, in comparison to standard chow, does not induce a spontaneous reduction in food intake.…”
Section: Behavioral Effects Of Kd Treatmentmentioning
confidence: 85%
“…Considering the low efficiency of the growth factor to stimulate the growth of colon cancer cells, the supplementation of a ketogenic diet is potential adjuvant therapy for colon cancer. The progression of colon cancer is systemic inflammation [30]. It has been reported that the ketogenic diet metabolite of the ketone body specifically β-hydroxybutyrate and acetoacetate acid can directly suppress co-lon cancer inflammation [31].…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%